2023
DOI: 10.1177/1532673x231175675
|View full text |Cite
|
Sign up to set email alerts
|

Campaigning Through Cable: Examining the Relationship Between Cable News Appearances and House Candidate Fundraising

Abstract: Appearances of elected officials on cable news have become a regular feature of American politics. Do candidates going on cable news see a subsequent bump in fundraising? We evaluate all television appearances for every major party candidate running for the House from 2009–2020 on CNN, MSNBC, and Fox News. We match these with FEC records of every individual campaign contribution made during the same period. We find evidence that candidates who appear on cable news do see a spike in fundraising on the day of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…These results emphasize media outlets' considerable influence and ideological orientations in shaping political preferences and voting decisions. The role of media in informing, persuading, and potentially biasing voters' choices is evident, reflecting the power of media consumption patterns in the political landscape (DellaVigna and Kaplan, 2005;Jones, 2020;Jurkowitz et al, 2020;Nelson, 2020;Stelter, 2020;Grant et al, 2021;Belcastro et al, 2022;Benson and Limbocker, 2023;Fujiwara et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…These results emphasize media outlets' considerable influence and ideological orientations in shaping political preferences and voting decisions. The role of media in informing, persuading, and potentially biasing voters' choices is evident, reflecting the power of media consumption patterns in the political landscape (DellaVigna and Kaplan, 2005;Jones, 2020;Jurkowitz et al, 2020;Nelson, 2020;Stelter, 2020;Grant et al, 2021;Belcastro et al, 2022;Benson and Limbocker, 2023;Fujiwara et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…For members of Congress, bill sponsorship (Rocca and Gordon 2010) and earmarking (Rocca and Gordon 2013) activities can be effective tools for generating campaign contributions from interest groups and lobbyists. Other work has shown that legislators can raise significant sums from donors simply by appearing on cable TV news (Benson and Limbocker 2023).…”
Section: The Consumer Modelmentioning
confidence: 99%